Peculiarities of anxiety among Ukrainian military personnel - OSADCHUK, Ruslan (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
The study of anxiety among the military is the most urgent problem of today. Military personnel bear a huge responsibility, their work is associated with significant danger to life, physical and mental overload. Prolonged exposure to such conditions can lead to an increase in anxiety. High levels of anxiety have a negative impact on the nature of their work and the performance of their duties. That is why the purpose of this article is to review the latest research on anxiety among Ukrainian military personnel.The following research methods were used: analysis, synthesis, comparison, systematization and generalization of psychological data on the research problem.The analysis allowed us to draw the following conclusions. Before the full-scale invasion in 2022, anxiety among the military was average, with no significant differences depending on the experience and time of involvement in the JFO. After the aggression in 2022, anxiety increased, exceeding the level during the COVID-19 pandemic. Male servicemen generally have lower levels of anxiety compared to female servicemen. The number of children of military personnel is negatively correlated with anxiety – the more children military personnel have, the less anxious the military personnel are. Volunteers in the territorial defense forces and those in the reserve had lower levels of anxiety compared to regular army personnel, even though they all participated in combat. Servicemen who are preparing to be deployed to a combat zone demonstrate an average level of situational anxiety.For servicemen who have been in combat for a long time, situational anxiety can develop into personal anxiety. Anxiety complicates the process of military rehabilitation, affects the emotional sphere and disrupts behavioral regulation. In some cases, it can lead to suicidal behavior.
Keywords: anxiety; military personnel; russian aggression; war